Adhesive tape

By adjusting the gel fraction and displacement of the adhesive layer, the retaining force of the adhesive tape on the shear direction load is improved, and the problem of peeling of existing adhesive tapes with large loads in large display devices is solved, achieving higher fixing strength and stability.

CN114787309BActive Publication Date: 2025-04-29SEKISUI CHEMICAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180006964.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-10
Filing Date
2021-02-09
Publication Date
2025-04-29
Estimated Expiration
2041-02-09

AI Technical Summary

Technical Problem

The existing adhesive tape is prone to peeling when the load on the shear direction is large, making it difficult to meet the fixing needs of the cover plate and the housing in large display devices.

Method used

By adjusting the gel fraction of the adhesive layer and the displacement amount at 80°C, the cohesion of the adhesive layer is sufficient, and the retaining force of the adhesive tape to the shear direction load is increased. The specific method includes adjusting the composition of (meth)acrylic copolymer, the type and amount of crosslinking agent, and polymerization conditions to achieve an optimized gel fraction and displacement range.

Benefits of technology

It significantly improves the retention force of the adhesive tape to the shear direction load, reduces the occurrence of peeling, and is suitable for the fixing needs of large display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114787309B_ABST
    Figure CN114787309B_ABST
Patent Text Reader

Abstract

The present invention aims to provide an adhesive tape having a high holding force against a load in a shear direction. The present invention is an adhesive tape having an adhesive layer, wherein the gel fraction of the adhesive layer is 25% by weight or more and 70% by weight or less, and the displacement per 1 μm thickness of the adhesive layer measured at 80° C. using a cohesion tester is 3.8 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to adhesive tapes. Background Art

[0002] Adhesive tapes are widely used for fixing electronic components. Specifically, in display devices such as televisions and monitors, adhesive tapes are used to fix a cover plate on a surface to a housing. Such adhesive tapes are used in a manner such as being arranged around a display screen in a shape such as a frame.

[0003] In recent years, the pursuit of design and functionality has resulted in narrower bezels for display devices such as televisions and monitors, and expectations for bezel-less display devices are also increasing. In the manufacture of previous display devices, the cover plate is sometimes fixed to the housing by embedding or screwing, but embedding and screwing are difficult in display devices with narrower bezels, so there is an increasing demand for fixing using adhesive tapes, and the thinning and narrowing of adhesive tapes are also being promoted.

[0004] As an adhesive tape that can be used in such a display device, for example, Patent Documents 1 and 2 describe an impact-absorbing tape that is a cross-linked polyolefin resin foam sheet in which an acrylic adhesive layer is laminated and integrated on at least one side of a substrate layer, and the substrate layer has a specific degree of cross-linking and aspect ratio of bubbles.

[0005] However, as display devices such as televisions and monitors continue to grow in size, the weight of fixed components such as covers and housings has also increased. Therefore, a much larger load than before is applied to the adhesive tape in the shear direction, which particularly causes the problem of peeling when the adhesive tape is used in a thin and narrow width.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2009-242541

[0009] Patent Document 2: Japanese Patent Application Publication No. 2009-258274 Summary of the invention

[0010] Problems to be solved by the invention

[0011] An object of the present invention is to provide a pressure-sensitive adhesive tape that exhibits a high holding force against a load in a shearing direction.

[0012] Means for solving problems

[0013] The present invention provides an adhesive tape having an adhesive layer having a gel fraction of 25 wt % to 70 wt % and a displacement per 1 μm thickness of the adhesive layer measured at 80° C. using a cohesion tester of 3.8 μm or less.

[0014] The present invention is described in detail below.

[0015] The present inventors have discovered that, in an adhesive tape having an adhesive layer, by adjusting the gel fraction of the adhesive layer and the displacement per 1 μm thickness of the adhesive layer measured at 80° C. using a cohesion tester to a specific range, the holding force against a load in the shear direction can be significantly improved, thereby completing the present invention.

[0016] The pressure-sensitive adhesive tape of the present invention includes a pressure-sensitive adhesive layer, and the lower limit of the gel fraction of the pressure-sensitive adhesive layer is 25% by weight and the upper limit is 70% by weight.

[0017] If the gel fraction is 25% by weight or more, the cohesive force of the adhesive layer becomes sufficiently high, and the holding force of the adhesive tape to the load in the shear direction becomes high. If the gel fraction is 70% by weight or less, the wettability of the adhesive layer to the adherend becomes sufficient, and the holding force of the adhesive tape to the load in the shear direction becomes high. The preferred lower limit of the gel fraction is 35% by weight, the preferred upper limit is 65% by weight, the more preferred lower limit is 45% by weight, and the more preferred upper limit is 60% by weight.

[0018] In addition, the gel fraction of the pressure-sensitive adhesive layer can be measured by the following method.

[0019] The adhesive tape was cut into a flat rectangle of 50 mm × 100 mm to prepare a test piece. The test piece was shaken in ethyl acetate at 23°C and 120 rpm for 24 hours. After shaking, the ethyl acetate was separated from the test piece that had absorbed ethyl acetate and swelled using a metal mesh (mesh size #200), and the separated test piece and the metal mesh were dried at 110°C for 1 hour. After drying, the test piece was placed at 23°C for 30 minutes, and after the temperature of the test piece was restored to 23°C, the weight of the test piece was measured, and the gel fraction was calculated using the following formula (1).

[0020] In addition, the release film for protecting the adhesive layer was not laminated on the test piece. As the test piece, an adhesive composition obtained by scraping off only 0.1 g of the adhesive layer of the adhesive tape may be used.

[0021] Gel fraction (weight %) = 100 × (W2-W0-W3) / (W1-W0) (1)

[0022] (W0: weight of substrate, W1: weight of test piece before immersion, W2: weight of test piece including metal mesh after immersion and drying, W3: initial weight of metal mesh)

[0023] The method for adjusting the gel fraction of the above-mentioned adhesive layer to the above-mentioned range is not particularly limited, and examples thereof include: a method of adjusting the composition, weight average molecular weight (Mw), molecular weight distribution (Mw / Mn), etc. of the (meth)acrylic copolymer contained in the above-mentioned adhesive layer; a method of adjusting the type and amount of the cross-linking agent contained in the above-mentioned adhesive layer; a method of adjusting the curing time and temperature when forming the above-mentioned adhesive layer, etc.

[0024] More specifically, when the composition of the (meth)acrylic copolymer contained in the adhesive layer is adjusted, for example, by increasing the amount of the structural unit derived from the monomer having a crosslinking functional group (functional monomer), the gel fraction of the adhesive layer can be increased. In addition, when the type and amount of the crosslinking agent contained in the adhesive layer are adjusted, for example, by using an isocyanate crosslinking agent, an aziridine crosslinking agent, an epoxy crosslinking agent, a metal chelate crosslinking agent, etc. or by increasing the amount of the crosslinking agent, the gel fraction of the adhesive layer can be increased.

[0025] It should be noted that, in the present specification, "(meth)acrylic acid" means acrylic acid or methacrylic acid, and other similar terms are the same.

[0026] The upper limit of the displacement amount per 1 μm thickness of the pressure-sensitive adhesive layer measured at 80° C. using a cohesion tester is 3.8 μm.

[0027] The deformation of the adhesive layer at 80°C (high temperature) is equivalent to the deformation when a load is applied to the adhesive layer at a low speed. If the displacement is 3.8 μm or less, the cohesive force of the adhesive layer becomes sufficiently high, and the holding force of the adhesive tape against the load in the shear direction becomes high. The preferred upper limit of the displacement is 3.4 μm, and the more preferred upper limit is 3 μm. The lower limit of the displacement is not particularly limited, but if it is too low, the wettability of the adhesive layer to the adherend is reduced, so the preferred lower limit is 0.5 μm, and the more preferred lower limit is 0.8 μm.

[0028] The displacement amount per 1 μm thickness of the pressure-sensitive adhesive layer measured at 80° C. using a cohesion tester can be measured by the following method.

[0029] Figure 1 A schematic diagram showing a cohesion test of an adhesive layer is shown. Figure 1As shown, after the adhesive tape 8 is cut into 20mm×40mm, the release film on one side is peeled off, and a 30mm×150mm PET film 12 (for example, FE2002 manufactured by Futamura Chemical Co., Ltd., with a thickness of 23μm) is respectively attached to the two ends of the exposed adhesive layer (the two ends in the length direction of 40mm). At this time, the two ends of the adhesive tape 8 are attached to the PET film 12 in a manner that each overlaps 5mm. Then, the center of the adhesive tape 8 is attached to a SUS plate 11 with a width of 5mm heated to 80°C. A 100g weight 13a is fixed to the end of the side of the two PET films 12 where the adhesive tape 8 is not attached. A 200g weight 13b is fixed to the end of one PET film 12, and a static load is applied in the horizontal direction for 3 minutes. The displacement of the adhesive tape 8 in the tensile direction is measured using an electronic micrometer 14, and the displacement is divided by the thickness of the adhesive layer to calculate the displacement of the adhesive layer per 1μm thickness.

[0030] The method for adjusting the displacement amount to the above range is not particularly limited. The inventors of the present invention conducted a multiple correlation analysis and found that, among various factors, the gel fraction of the adhesive layer and the molecular weight distribution (Mw / Mn) of the (meth)acrylic copolymer contained in the adhesive layer are particularly important for adjusting the displacement amount. That is, as a method for adjusting the displacement amount to the above range, preferably, a method for adjusting the gel fraction of the adhesive layer to the above range and a method for adjusting the molecular weight distribution (Mw / Mn) of the (meth)acrylic copolymer contained in the adhesive layer to the range described below (that is, reducing the molecular weight distribution (Mw / Mn)) are used.

[0031] The method of reducing the molecular weight distribution (Mw / Mn) of the (meth)acrylic copolymer contained in the pressure-sensitive adhesive layer is not particularly limited, and an example thereof includes a method of using a (meth)acrylic copolymer obtained by living radical polymerization.

[0032] Living radical polymerization is a polymerization in which the molecular chain grows without being hindered by side reactions such as termination reactions or chain transfer reactions. In living radical polymerization, the growing terminal radicals are not deactivated, and no new radical species are generated during the reaction, and the reaction proceeds. In the middle of the reaction, all molecular chains polymerize while reacting uniformly with the monomers, and the composition of all molecular chains is close to uniform.

[0033] Therefore, according to living radical polymerization, a copolymer having a more uniform molecular weight and composition can be obtained compared with free radical polymerization, and the generation of low molecular weight components and the like can be suppressed, so that the molecular weight distribution (Mw / Mn) can be easily reduced.

[0034] On the other hand, in free radical polymerization, free radical species are continuously generated during the reaction and added to the monomer to polymerize. Therefore, in free radical polymerization, molecular chains are generated in which the terminal free radicals are deactivated in the middle of the reaction and molecular chains grow due to free radical species newly generated during the reaction.

[0035] Therefore, according to the radical polymerization, the composition of the copolymer becomes non-uniform compared with the living radical polymerization, and also includes a copolymer having a low molecular weight.

[0036] However, from the viewpoint of shortening the reaction time and suppressing the cost, free radical polymerization is preferably used rather than living radical polymerization.

[0037] As a method of reducing the molecular weight distribution (Mw / Mn) while using a (meth)acrylic acid copolymer obtained by free radical polymerization, for example, a method of using a (meth)acrylic acid copolymer obtained by keeping the polymerization temperature and the concentration of the monomer mixture constant in free radical polymerization, etc. As a polymerization method to achieve such a relatively mild polymerization condition, for example, a method of performing constant temperature polymerization, a method of initiating polymerization by adding half of the monomer mixture and a polymerization initiator to a reaction vessel in boiling point polymerization, and then adding the remaining half of the monomer mixture dropwise or all at once, etc. In addition, a method of performing polymerization at a relatively low polymerization temperature (for example, about 56°C) by using a solvent with a relatively low boiling point (for example, acetone, methyl ethyl ketone (MEK), etc.) as a polymerization solvent, etc., etc., can also be mentioned. In addition, a method of performing polymerization by stopping the reaction in the middle of the polymerization and reducing the reaction rate in a short time (for example, 1 to 5 hours), etc. can also be mentioned.

[0038] By adopting a method of stopping the reaction in the middle of the polymerization to reduce the reaction rate in a short time (e.g., 1 to 5 hours) and polymerizing, it is possible to reduce the molecular weight distribution (Mw / Mn) while using the (meth)acrylic acid copolymer obtained by free radical polymerization, and further shorten the reaction time or further reduce the cost. It should be noted that when such a method is adopted, the content of volatile components derived from monomers constituting the (meth)acrylic acid copolymer described later in the adhesive layer will easily meet the range described later.

[0039] The adhesive layer is not particularly limited, and examples thereof include adhesive layers comprising (meth)acrylic adhesives, rubber adhesives, urethane adhesives, silicone adhesives, etc. Among them, an adhesive layer comprising a (meth)acrylic adhesive containing a (meth)acrylic copolymer and a tackifier is preferred because the adhesive force can be easily adjusted, it is relatively stable to light, heat, moisture, etc., and it can be applied to various adherends.

[0040] The (meth)acrylic acid-based copolymer may contain a structural unit derived from an alkyl (meth)acrylate having an alkyl group having 3 or less carbon atoms. In this case, the content of the structural unit is preferably 20% by weight or less.

[0041] Examples of the alkyl (meth)acrylate having an alkyl group with a carbon number of 3 or less include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, etc. These alkyl (meth)acrylates having an alkyl group with a carbon number of 3 or less may be used alone or in combination of two or more.

[0042] If the content of the structural unit derived from the alkyl (meth)acrylate having an alkyl group with a carbon number of 3 or less is 20% by weight or less, the cohesive force of the adhesive layer is improved, and the holding force of the adhesive tape against a load in the shear direction is increased. The upper limit of the content of the structural unit is more preferably 10% by weight, and the upper limit is still more preferably 5% by weight.

[0043] The (meth)acrylic acid-based copolymer may contain a structural unit derived from 2-ethylhexyl acrylate.

[0044] The content of the structural unit derived from 2-ethylhexyl acrylate is not particularly limited, and the preferred upper limit is 60% by weight. If the content of the structural unit is less than 60% by weight, the cohesive force of the adhesive layer is improved, and the holding force of the adhesive tape to the load in the shear direction becomes higher. The lower limit of the content of the structural unit is not particularly limited, and can be 0% by weight.

[0045] The (meth)acrylic copolymer may contain a structural unit derived from another copolymerizable polymerizable monomer other than the structural unit derived from the (meth)acrylic acid alkyl ester having an alkyl group with 3 or less carbon atoms and the structural unit derived from 2-ethylhexyl acrylate, as necessary.

[0046] Examples of the other copolymerizable monomers include (meth)acrylic acid alkyl esters having an alkyl group having 13 to 18 carbon atoms and functional monomers.

[0047] Examples of the alkyl (meth)acrylate having an alkyl group with 13 to 18 carbon atoms include tridecyl methacrylate and stearyl (meth)acrylate. Examples of the functional monomer include hydroxyalkyl (meth)acrylate, glycerol dimethacrylate, glycidyl (meth)acrylate, 2-methacryloyloxyethyl isocyanate, (meth)acrylic acid, itaconic acid, maleic anhydride, crotonic acid, maleic acid, and fumaric acid.

[0048] These other copolymerizable polymerizable monomers may be used alone or in combination of two or more.

[0049] The (meth) acrylic copolymer may contain a structural unit derived from acrylic acid. The content of the structural unit derived from acrylic acid is not particularly limited, and the preferred lower limit is 3% by weight. If the content of the structural unit is 3% by weight or more, the cohesive force of the adhesive layer is improved, and the holding force of the adhesive tape to the load in the shear direction becomes higher. The more preferred lower limit of the content of the structural unit is 5% by weight. The upper limit of the content of the structural unit is not particularly limited, and the preferred upper limit is 10% by weight.

[0050] The (meth)acrylic acid copolymer is obtained by copolymerizing a monomer mixture. In order to copolymerize the monomer mixture to obtain the (meth)acrylic acid copolymer, the monomer mixture may be subjected to a free radical reaction in the presence of a polymerization initiator. As a method for subjecting the monomer mixture to a free radical reaction, i.e., a polymerization method, a conventionally known method may be used, for example, solution polymerization (boiling point polymerization or constant temperature polymerization), emulsion polymerization, suspension polymerization, bulk polymerization, etc. As a reaction mode when subjecting the monomer mixture to a free radical reaction, for example, living free radical polymerization, free radical polymerization, etc. as described above may be mentioned.

[0051] Examples of the polymerization initiator include organic peroxides and azo compounds.

[0052] Examples of the organic peroxide include 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyisobutyrate, tert-butyl peroxy-3,5,5-trimethylhexanoate, and tert-butyl peroxylaurate.

[0053] The azo compound is not particularly limited as long as it is an azo compound generally used for radical polymerization. Examples of the azo compound include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1-azobis(cyclohexane-1-carbonitrile), 1-[(1-cyano-1-methylethyl)azo]formamide, 4,4'-azobis(4-cyanovaleric acid), dimethyl-2,2'-azobis(2-methylpropionate), dimethyl-1,1'-azobis(1-cyclohexanecarboxylate), 2,2'-azobis{2-methyl-N-[1,1'-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis [N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl]propane} dihydrochloride , 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] tetrahydrate, 2,2'-azobis(1-imino-1-pyrrolidino-2-methylpropane) dihydrochloride, 2,2'-azobis(2,4,4-trimethylpentane), etc.

[0054] These polymerization initiators may be used alone or in combination of two or more.

[0055] When the monomer mixture is subjected to a radical reaction, a dispersion stabilizer may be used. Examples of the dispersion stabilizer include polyvinyl pyrrolidone, polyvinyl alcohol, methyl cellulose, ethyl cellulose, poly(meth)acrylic acid, poly(meth)acrylate, and polyethylene glycol.

[0056] When a polymerization solvent is used when the above-mentioned monomer mixture is subjected to a free radical reaction, the polymerization solvent is not particularly limited. As the above-mentioned polymerization solvent, for example, non-polar solvents such as hexane, cyclohexane, octane, toluene, and xylene can be used. In addition, as the above-mentioned polymerization solvent, for example, high-polarity solvents such as water, methanol, ethanol, propanol, butanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, tetrahydrofuran, dioxane, and N,N-dimethylformamide can be used. Among them, from the viewpoint of reducing the molecular weight distribution (Mw / Mn) while using the (meth) acrylic copolymer obtained by free radical polymerization, it is preferred to use a solvent with a lower boiling point as described above (for example, acetone, methyl ethyl ketone (MEK), etc.). These polymerization solvents can be used alone or in combination of two or more.

[0057] From the viewpoint of polymerization rate, the polymerization temperature is preferably 0 to 110° C. From the viewpoint of reducing the molecular weight distribution (Mw / Mn) while using the (meth)acrylic copolymer obtained by radical polymerization, it is more preferable to perform polymerization at a relatively low polymerization temperature (eg, about 56° C.) as described above.

[0058] The polymerization time is not particularly limited. However, from the viewpoint of reducing the molecular weight distribution (Mw / Mn) while using the (meth)acrylic acid-based copolymer obtained by free radical polymerization, it is more preferable to carry out the polymerization by stopping the reaction during the polymerization to reduce the reaction rate within a short time (eg, 1 to 5 hours) as described above.

[0059] The preferred lower limit of the weight average molecular weight (Mw) of the (meth) acrylic copolymer is 600,000, and the preferred upper limit is 2,000,000. If the weight average molecular weight is 600,000 or more, the adhesive layer has a moderate hardness, the cohesive force becomes sufficient, and the adhesive force becomes high. If the weight average molecular weight is 2,000,000 or less, the adhesive force of the adhesive layer becomes sufficient. The more preferred lower limit of the weight average molecular weight is 1,000,000, and the more preferred upper limit is 1,700,000. In order to adjust the weight average molecular weight to the above range, the polymerization conditions such as the polymerization initiator and the polymerization temperature can be adjusted.

[0060] The ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the (meth)acrylic copolymer (molecular weight distribution, Mw / Mn) is not particularly limited, but the upper limit is preferably 4.5. When the molecular weight distribution (Mw / Mn) of the (meth)acrylic copolymer is 4.5 or less, the content of low molecular weight components and the like is reduced, so that the displacement is likely to satisfy the above range, and the holding force of the adhesive tape against the load in the shear direction is increased. The upper limit of the molecular weight distribution (Mw / Mn) of the (meth)acrylic copolymer is more preferably 4.0, and the upper limit is still more preferably 3.5.

[0061] The number average molecular weight (Mn) and the weight average molecular weight (Mw) refer to molecular weights converted to standard polystyrene based on GPC (Gel Permeation Chromatography). For example, 2690 Separations Model (manufactured by Waters Corporation) can be used for GPC.

[0062] As the above-mentioned tackifier, for example, rosin ester resin, hydrogenated rosin resin, terpene resin, terpene phenol resin, coumarone indene resin, alicyclic saturated hydrocarbon resin, C5 petroleum resin, C9 petroleum resin, C5-C9 copolymer petroleum resin, etc. can be mentioned. These tackifiers can be used alone or in combination of two or more. In particular, from the aspect of being able to improve the adhesive force to various adherends, it is preferred to use two or more of the above-mentioned tackifiers in combination.

[0063] The above-mentioned thickener preferably contains a thickener having a hydroxyl value of 35 or more.

[0064] By including a tackifier having a hydroxyl value of 35 or more as the tackifier, when the polarity of the adherend is high, the wettability of the adhesive layer to the adherend is increased, and the holding force of the adhesive tape against the load in the shear direction is increased.

[0065] In addition, the hydroxyl value can be measured according to JIS K1557 (phthalic anhydride method).

[0066] Relative to the total amount of the above-mentioned tackifier, the content of the tackifier with a hydroxyl value of 35 or more is preferably 60% by weight or more. If the content of the tackifier with a hydroxyl value of 35 or more is 60% by weight or more, then in the case where the polarity of the adherend is high, the wettability of the above-mentioned adhesive layer to the adherend becomes higher, and the adhesive force of the above-mentioned adhesive layer and the holding force of the load in the shear direction of the adhesive tape become higher. The content of the tackifier with a hydroxyl value of 35 or more is more preferably 80% by weight or more. The upper limit of the content of the tackifier with a hydroxyl value of 35 or more is not particularly limited and can be 100% by weight.

[0067] The content of the tackifier is not particularly limited, but the preferred lower limit relative to 100 parts by weight of the (meth) acrylic copolymer is 10 parts by weight, and the preferred upper limit is 50 parts by weight. If the content of the tackifier is 10 parts by weight or more, the adhesive force of the adhesive layer becomes higher. If the content of the tackifier is 50 parts by weight or less, it is possible to suppress the situation where the adhesive layer becomes too hard and the anchoring property with the substrate is reduced. The more preferred lower limit of the content of the tackifier is 20 parts by weight, and the more preferred upper limit is 40 parts by weight.

[0068] The adhesive layer preferably forms a crosslinked structure between the main chains of the resin constituting the adhesive layer (e.g., the (meth)acrylic copolymer, the tackifier, etc.) by adding a crosslinking agent. By adjusting the type and amount of the crosslinking agent, the gel fraction and the displacement amount of the adhesive layer can be easily adjusted to the above ranges.

[0069] The crosslinking agent is not particularly limited, and examples thereof include isocyanate crosslinking agents, aziridine crosslinking agents, epoxy crosslinking agents, metal chelate crosslinking agents, etc. Among them, isocyanate crosslinking agents are preferred.

[0070] The amount of the crosslinking agent added is preferably 0.01 parts by weight, and the preferred upper limit is 10 parts by weight, based on 100 parts by weight of the (meth)acrylic copolymer. The more preferred lower limit is 0.1 parts by weight, and the more preferred upper limit is 3 parts by weight. The further preferred lower limit is 0.5 parts by weight, and the further preferred upper limit is 2 parts by weight.

[0071] The adhesive layer may contain a silane coupling agent for the purpose of improving adhesive strength. The silane coupling agent is not particularly limited, and examples thereof include epoxy silanes, acrylic silanes, methacrylic silanes, amino silanes, and isocyanate silanes.

[0072] The adhesive layer may contain a coloring material for the purpose of imparting light-shielding properties. The coloring material is not particularly limited, and examples thereof include carbon black, aniline black, titanium oxide, etc. Among them, carbon black is preferred because it is relatively inexpensive and chemically stable.

[0073] The haze value of the adhesive layer is not particularly limited, and the preferred upper limit is 30%. If the haze value is 30% or less, the compatibility of the resin constituting the adhesive layer (for example, the (meth) acrylic copolymer, the tackifier, etc.) becomes sufficient, the adhesive force of the adhesive layer can be improved, and the wettability to the adherend can also be improved. The more preferred upper limit of the haze value is 26%. The lower limit of the haze value is not particularly limited, and can be about 0%.

[0074] It should be noted that the haze value of the adhesive layer can be measured using a haze meter (e.g., Nippon Denshoku Industries, “NDH 4000”). The measurement sample is prepared as follows: the adhesive layer (thickness 50 μm) applied to the spacer is attached to a glass plate (e.g., S1214 MICRO SLIDE GLASS, Matsunami Glass Industries), and then the spacer is peeled off. It should be noted that the 0 point setting (calibration) is performed by setting only the glass plate to which the adhesive layer is attached. In the case where the adhesive layer contains a coloring material, the portion that does not contain the coloring material is measured as an object.

[0075] When the pressure-sensitive adhesive layer contains the (meth)acrylic acid-based copolymer, the content of volatile components derived from monomers constituting the (meth)acrylic acid-based copolymer is preferably 10 ppm or more.

[0076] By adopting the above-mentioned method of stopping the reaction in the middle of the polymerization and reducing the reaction rate in a short time (for example, 1 to 5 hours) to polymerize, it is possible to reduce the molecular weight distribution (Mw / Mn) while using the (meth)acrylic copolymer obtained by free radical polymerization, and further shorten the reaction time or further suppress the cost. Here, when such a method is adopted, the adhesive layer contains a large amount of residual monomers that are not consumed during the polymerization of the (meth)acrylic copolymer. When the content of volatile components from the monomers constituting the (meth)acrylic copolymer is 10ppm or more, it can be considered that the content of the residual monomers is large, and it is considered that a method of stopping the reaction in the middle of the polymerization and reducing the reaction rate in a short time to polymerize is adopted. In such a case, it is possible to reduce the molecular weight distribution (Mw / Mn) while using the (meth)acrylic copolymer obtained by free radical polymerization, so the displacement is easy to meet the above range, the holding force of the adhesive tape relative to the load in the shear direction becomes higher, and the reaction time can be further shortened or the cost can be further suppressed. The more preferred lower limit of the content of the volatile component is 100ppm.

[0077] The upper limit of the content of the volatile component is not particularly limited. If it is too high, the displacement amount will hardly satisfy the above range, and the holding force of the pressure-sensitive adhesive tape against a load in the shear direction will decrease. Therefore, the upper limit is preferably 6000 ppm.

[0078] The monomer constituting the (meth)acrylic copolymer is not particularly limited, and may be the (meth)acrylic acid alkyl ester having an alkyl group with 3 or less carbon atoms, 2-ethylhexyl acrylate, (meth)acrylic acid alkyl ester having an alkyl group with 13 to 18 carbon atoms, a functional monomer, or the like.

[0079] In addition, the content of the volatile component derived from the monomer of the (meth)acrylic-based copolymer constituting the pressure-sensitive adhesive layer can be measured by the following method.

[0080] The weighed adhesive tape or the adhesive composition obtained by scraping the adhesive layer is heated at 90° C. for 30 minutes using a thermal desorption device (e.g., “Gerstel TDS” manufactured by Gestel). The amount of volatile components released at this time is measured using a GC-MS device (e.g., “Agilent 6890GC / 5973MSD” manufactured by Agilent Technologies), and the content of the volatile components is calculated by the following formula (2).

[0081] Content of volatile components (ppm) = Total amount of volatile components derived from monomers of the (meth)acrylic copolymer constituting the adhesive layer (μg) / weight of adhesive before heating (g) (2)

[0082] It should be noted that the weight of the adhesive before heating is obtained, for example, by finding the weight ratio of the PET film as the substrate in the adhesive tape and subtracting the weight of the substrate from the weight of the adhesive tape (weight of the adhesive=weight of the adhesive tape-weight of the substrate). For the PET film, it is confirmed in advance that the volatile components from the monomers constituting the (meth)acrylic copolymer contained in the adhesive layer are not released. Alternatively, an adhesive composition obtained by scraping only about 10 mg of the adhesive layer of the adhesive tape can also be used.

[0083] More specifically, the content of the volatile component derived from the monomer of the (meth)acrylic copolymer constituting the pressure-sensitive adhesive layer can be measured by, for example, the following method.

[0084] An adhesive tape (3 mm × 45 mm) having a PET film as a substrate and an adhesive layer is placed in a sample tube (4 mm inner diameter, 18 cm length). Helium is circulated at 1.3 mL / min for 30 minutes while being heated and maintained at 90°C, and the obtained volatile components are collected in a collection tube built into a thermal desorption device (e.g., "Gerstel TDS" manufactured by Gestel) for concentration. The collection tube is then heated at 280°C for 5 minutes and introduced into a GC-MS device (e.g., "Agilent 6890GC / 5973MSD" manufactured by Agilent Technologies). A non-polar capillary column (e.g., "Ultra2" (0.32 mm × 50 m × 0.52 μm) manufactured by Agilent Technologies, etc.) is used in the GC-MS measurement. The column temperature was maintained at 40°C for 2 minutes, then raised to 92°C at a rate of 3°C per minute, raised to 160°C at a rate of 5°C per minute, raised to 280°C at a rate of 10°C per minute, and then maintained at 280°C for 10 minutes. The MS measurement range was set to 29-400 amu, the He flow rate was set to 1.3 mL / min, the ionization voltage was set to 70 eV, the ion source was set to 230°C, the interface was set to 280°C, and the transfer line was set to 280°C.

[0085] The volatile content is calculated by weight conversion of the obtained peak area based on an absolute calibration curve prepared with toluene. It should be noted that the volatile components are derived from the monomers constituting the (meth)acrylic copolymer, which can be confirmed by analyzing the adhesive layer by infrared spectroscopy, GC / MS, etc.

[0086] The thickness of the adhesive layer is not particularly limited, and the preferred lower limit of the thickness of the adhesive layer on one side is 20 μm, and the preferred upper limit is 100 μm. If the thickness of the adhesive layer is 20 μm or more, the adhesive force of the adhesive layer becomes sufficient. If the thickness of the adhesive layer is 100 μm or less, the stress relaxation of the substrate can also fully contribute to the stress relaxation of the adhesive tape as a whole. The more preferred lower limit of the thickness of the adhesive layer is 30 μm, and the more preferred upper limit is 80 μm.

[0087] The thickness of the pressure-sensitive adhesive layer can be measured using a dial thickness gauge (for example, “ABS Digital Indicator” manufactured by Mitutoyo Corporation).

[0088] The pressure-sensitive adhesive tape of the present invention preferably further has a substrate.

[0089] In this case, the adhesive layer may be laminated on one side or on both sides of the substrate. The adhesive layers laminated on both sides of the substrate may have the same composition or different compositions.

[0090] The substrate is not particularly limited, but is preferably a foam substrate.

[0091] The foam substrate has a moderate flexibility that can release stress, so the stress relaxation property of the adhesive tape is improved by having the foam substrate. As a result, the impact resistance of the adhesive tape is improved, and when the adhesive tape is used to fix components in a display device such as a television or a monitor, the display unevenness of the display device can be reduced.

[0092] The foam substrate may have a single-layer structure or a multi-layer structure.

[0093] The foam substrate is not particularly limited, and examples thereof include polyurethane foam, polyolefin foam, acrylic foam, etc. Among them, polyurethane foam is preferred because it has appropriate flexibility.

[0094] Examples of the polyurethane foam include polyurethane foams made of a urethane resin composition containing polyisocyanate and polyol. Such a polyurethane foam can be produced by heat-curing the urethane resin composition.

[0095] The polyisocyanate is not particularly limited, and examples thereof include aromatic polyisocyanates or aliphatic polyisocyanates commonly used in polyurethane foams, among which aromatic diisocyanates or aliphatic diisocyanates having two isocyanate groups in one molecule are preferred.

[0096] By using the above polyisocyanate as the above aromatic diisocyanate or aliphatic diisocyanate, the crosslinking degree of the above polyurethane foam will not be excessively increased, and the glass transition temperature (Tg) will become lower, so that the foam becomes easily stretchable. Thus, the strength becomes sufficiently high without impairing the flexibility of the above polyurethane foam, and it is easy to balance the stress relaxation property of the adhesive tape and the holding force against the load in the shear direction.

[0097] Specific examples of the above aromatic diisocyanate or aliphatic diisocyanate include, for example: 4,4'-diphenylmethane diisocyanate, toluene diisocyanate, 1,6-hexamethylene diisocyanate, 1,5-naphthalene diisocyanate, p-phenylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, m-xylylene diisocyanate, hexamethylene diisocyanate, hydrogenated MDI, isophorone diisocyanate, etc. It should be noted that 4,4'-diphenylmethane diisocyanate is usually also referred to as "MDI" or "biphenyl monomer MDI (Japanese: 2-core monomeric MDI)". Among them, from the aspect of easily obtaining a polyurethane foam with excellent flexibility, 4,4'-diphenylmethane diisocyanate (MDI) is preferred. These aromatic diisocyanates or aliphatic diisocyanates can be used alone or in combination of two or more.

[0098] The above polyisocyanate may have three or more isocyanate groups in one molecule. Examples of such polyisocyanates include polymeric MDI, etc. As the above polyisocyanate, urethane prepolymers having isocyanate groups can also be further cited. These polyisocyanates can be used alone or in combination of two or more.

[0099] The above polyol is not particularly limited, and polyols used in ordinary polyurethane foams can be cited. Specifically, for example, polyether polyols, polyester polyols, polyether ester polyols, etc. can be cited. In addition, as the above polyol, trifunctional polyether polyols, glycerol, trimethylolpropane, etc. can also be cited. These polyols can be used alone or in combination of two or more.

[0100] The above polyether polyol is not particularly limited, and polypropylene glycol (PPG), etc. can be cited. The above polyester polyol is not particularly limited, and a polyester polyol formed from a polyol component and an acid component can be used.

[0101] The above polyol preferably contains short-chain diols. By making the above polyol contain the above short-chain diols, the strength becomes sufficiently high without impairing the flexibility of the above polyurethane foam, and it is easy to balance the stress relaxation property of the adhesive tape and the holding force against the load in the shear direction.

[0102] Examples of the short-chain diols include 1,5-pentanediol, 1,6-hexamethylene glycol, neopentyl glycol, ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,4-butanediol, and neopentyl glycol. These short-chain diols may be used alone or in combination of two or more. Among them, 1,5-pentanediol or 1,6-hexamethylene glycol is preferred from the perspective of easily obtaining a high-strength polyurethane foam.

[0103] The weight average molecular weight of the above-mentioned polyol is not particularly limited, and the preferred lower limit is 500, and the preferred upper limit is 5000. If the weight average molecular weight of the above-mentioned polyol is more than 500, the above-mentioned polyurethane foam can have appropriate flexibility. If the weight average molecular weight of the above-mentioned polyol is less than 5000, the excessive reduction of the intensity of the above-mentioned polyurethane foam can be suppressed. The more preferred lower limit of the weight average molecular weight of the above-mentioned polyol is 700, the more preferred upper limit is 2000, the further preferred lower limit is 800, and the further preferred upper limit is 1500.

[0104] The weight average molecular weight of the polyol can be measured, for example, by preparing a tetrahydrofuran solution of the sample and then using a GPC apparatus (eg, manufactured by Tosoh Corporation, product name “HLC-8220”, columns: TSK gelSurper HZM-N (4 columns)).

[0105] The isocyanate index of the polyisocyanate in the urethane resin composition is not particularly limited, but a preferred lower limit is 70 and a preferred upper limit is 120.

[0106] The isocyanate index is an index of isocyanate equivalents in the reaction of isocyanate with an active hydrogen-containing compound. When the isocyanate index is less than 100, it means that reactive groups such as hydroxyl groups are in excess of isocyanate groups, and when the isocyanate index exceeds 100, it means that isocyanate groups are in excess of reactive groups such as hydroxyl groups.

[0107] If the isocyanate index is 70 or more, the crosslinking based on the polyisocyanate becomes sufficient, and the polyurethane foam can have a moderate density. If the isocyanate index is 120 or less, the crosslinking degree of the polyurethane foam will not be excessively increased, and the glass transition temperature (Tg) becomes lower, so that the polyurethane foam is easily elongated. In either case, it is easy to take into account both the stress relaxation property of the adhesive tape and the holding power of the load in the shear direction.

[0108] The content of the polyisocyanate in the urethane resin composition is not particularly limited, and relative to 100% by weight of the polyol, the preferred lower limit is 5% by weight, and the preferred upper limit is 15% by weight. If the content of the polyisocyanate is more than 5% by weight, then the crosslinking based on the polyisocyanate becomes sufficient, and the polyurethane foam can have a moderate density. If the content of the polyisocyanate is less than 15% by weight, the crosslinking degree of the polyurethane foam will not be excessively improved, and the glass transition temperature (Tg) becomes relatively low, so it becomes a foam that is easily elongated. In either case, it is easy to take into account both the stress relaxation of the adhesive tape and the holding power of the load in the shear direction.

[0109] The urethane resin composition may contain a catalyst as necessary.

[0110] Examples of the catalyst include organotin compounds, organozinc compounds, organonickel compounds, organoferric compounds, metal catalysts, tertiary amine catalysts, and organic acid salts. Among them, organotin compounds are preferred. These catalysts may be used alone or in combination of two or more.

[0111] The amount of the catalyst added is not particularly limited, but the preferred lower limit is 0.05 parts by weight, the preferred upper limit is 5.0 parts by weight, and the more preferred upper limit is 4.0 parts by weight, relative to 100 parts by weight of the polyol.

[0112] Examples of the above-mentioned organic tin compound include stannous octoate, dibutyltin diacetate, dibutyltin dilaurate, etc. Examples of the above-mentioned organic zinc compound include zinc octoate, etc. Examples of the above-mentioned organic nickel compound include nickel acetylacetonate, nickel diacetylacetonate, etc. Examples of the above-mentioned organic iron compound include iron acetylacetonate, etc. Examples of the above-mentioned metal catalyst include alkali metal or alkaline earth metal alkoxides and phenolates, etc. Examples of the above-mentioned tertiary amine catalyst include triethylamine, triethylenediamine, N-methylmorpholine dimethylaminomethylphenol, imidazole, 1,8-diazabicyclo[5.4.0]undecene, etc.

[0113] The urethane resin composition may contain a foaming agent as necessary.

[0114] Examples of the foaming agent include foaming agents commonly used in polyurethane foams, and specific examples thereof include water, pentane, cyclopentane, hexane, cyclohexane, methylene chloride, and carbon dioxide.

[0115] The amount of the foaming agent added is not particularly limited, and may be an appropriate amount. When the foaming agent is water, the amount is usually about 0.1 to 3 parts by weight based on 100 parts by weight of the polyol.

[0116] The urethane resin composition may contain a foam stabilizer as necessary.

[0117] As the foam stabilizer, for example, silicone foam stabilizers such as dimethyl siloxane, polyether dimethyl siloxane, and phenyl methyl siloxane can be cited. Among them, polyether dimethyl siloxane is preferred. Among the polyether dimethyl siloxanes, block copolymers of dimethyl polysiloxane and polyether are more preferred. These foam stabilizers can be used alone or in combination of two or more.

[0118] The amount of the foam stabilizer added is not particularly limited, but the preferred lower limit is 0.2 parts by weight, the preferred upper limit is 7 parts by weight, the more preferred lower limit is 0.4 parts by weight, and the more preferred upper limit is 5 parts by weight, relative to 100 parts by weight of the polyol.

[0119] The urethane resin composition may contain additives generally used in the production of polyurethane foams, such as ultraviolet absorbers, antioxidants, organic fillers, inorganic fillers, and colorants, as necessary.

[0120] As a method for manufacturing the above-mentioned polyurethane foam, for example, a method (mechanical foaming method) can be cited in which a urethane resin composition (liquid) mechanically mixed with air, nitrogen, etc. and foamed is applied to the surface of a release liner or a resin film, and the coated urethane resin composition is heated and cured, thereby manufacturing a foam. In addition, a method (chemical foaming method) can be cited in which the above-mentioned polyisocyanate is reacted with a raw material for forming the above-mentioned polyurethane foam to generate gas. Among them, the mechanical foaming method is preferred. The polyurethane foam obtained by the mechanical foaming method is easy to become high-density compared to the polyurethane foam obtained by the chemical foaming method, and the bubble structure is easy to become fine and uniform.

[0121] Examples of the polyolefin foam include foams made of resins such as polyethylene resins, polypropylene resins, and polybutadiene resins. Among them, polyethylene resins are preferred because a soft polyolefin foam can be easily obtained.

[0122] The density of the foam substrate is not particularly limited, but the preferred lower limit is 100 kg / m 3 The preferred upper limit is 1000 kg / m 3 If the density of the foam substrate is 100 kg / m 3 If the density of the foam substrate is 1000 kg / m 3 The foam substrate can have appropriate softness if the density of the foam substrate is less than 100 kg / m. The more preferred lower limit of the density of the foam substrate is 120 kg / m 3 The more preferred upper limit is 800 kg / m3 .

[0123] When the foam substrate is the polyurethane foam, the lower limit of the density of the polyurethane foam is preferably 170 kg / m 3 The preferred upper limit is 650 kg / m 3 The more preferred lower limit is 280 kg / m 3 The more preferred upper limit is 500 kg / m 3 , and the further preferred lower limit is 400kg / m 3 .

[0124] The density can be measured using an electronic densitometer (eg, “ED120T” manufactured by MIRAGE) in accordance with JIS K 6401 (when polyurethane is used) or JIS K 6767 (when polyethylene is used).

[0125] The 25% compressive strength of the foam substrate is not particularly limited, and the preferred lower limit is 5kPa, and the preferred upper limit is 85kPa. If the 25% compressive strength of the foam substrate is 5kPa or more, the strength of the foam substrate is sufficiently increased. If the 25% compressive strength of the foam substrate is 85kPa or less, the foam substrate can have appropriate flexibility, and can also be pressed against the adhesive tape well. The more preferred lower limit of the 25% compressive strength of the foam substrate is 15kPa, and the more preferred upper limit is 70kPa.

[0126] In particular, when the foam substrate is the polyurethane foam, the preferred lower limit of the 25% compressive strength of the polyurethane foam is 10 kPa, and the preferred upper limit is 40 kPa.

[0127] In addition, the 25% compressive strength can be obtained by measuring in accordance with JIS K 6254.

[0128] When the foam substrate is the polyurethane foam, it is preferred that the density of the polyurethane foam is 240 kg / m 3 At least one of the above and the 25% compressive strength of the polyurethane foam is 15 kPa or more. By adjusting in this way, the holding force of the adhesive tape against the load in the shear direction becomes high.

[0129] The shear fracture strength of the foam substrate is not particularly limited, and the preferred lower limit is 80N / 25mm. If the shear fracture strength of the foam substrate is 80N / 25mm or more, the strength of the foam substrate is sufficiently increased, and the holding force of the adhesive tape to the load in the shear direction is further increased. The more preferred lower limit of the shear fracture strength of the foam substrate is 100N / 25mm, the further preferred lower limit is 300N / 25mm, and the particularly preferred lower limit is 400N / 25mm. The upper limit of the shear fracture strength of the foam substrate is not particularly limited. If it is too high, the softness of the foam substrate is reduced, so the preferred upper limit is 500N / 25mm.

[0130] The method for adjusting the shear fracture strength of the foam substrate to the above range is not particularly limited, and examples thereof include a method of adjusting the density, expansion ratio, gel fraction, and the like of the foam substrate.

[0131] In addition, the shear fracture strength of the foam substrate can be measured by the following method.

[0132] Figure 2 A schematic diagram showing a method for measuring the shear fracture strength of a foam substrate is shown. First, an adhesive tape having adhesive layers on both sides of a foam substrate is prepared, and a test piece 18 of the adhesive tape having a size of 25 mm×25 mm and two SUS plates 19 having a size of 125 mm×50 mm and a thickness of 2 mm are placed on the surface of the foam substrate. Figure 2 The laminate was pressed with a weight under the conditions of 5 kg for 10 seconds and then left to stand for 24 hours to prepare a test sample having two SUS plates 19 bonded with a test piece 18 interposed therebetween. After one SUS plate 19 of the test sample was fixed, the upper side of the other SUS plate 19 was stretched at 12.7 mm / min in a direction perpendicular to the stacking direction of the SUS plates (direction of the arrow in the figure) at 23°C, and the force applied to the test piece 18 when the test piece 18 broke (breaking point strength) was measured.

[0133] It should be noted that the fracture of the test piece 18 refers to the occurrence of interlayer failure (tearing) of the foam substrate. As the adhesive layers on both sides of the foam substrate, adhesive layers with an adhesive force that does not peel off at the interface between the adhesive layer and the SUS plate 19 before the occurrence of interlayer failure (tearing) of the foam substrate are used.

[0134] The glass transition temperature of the foam substrate is not particularly limited, and the preferred lower limit is -30°C, and the preferred upper limit is 30°C. If the glass transition temperature of the foam substrate is above -30°C, the foam substrate exhibits good low resilience and can relieve stress. If the glass transition temperature of the foam substrate is below 30°C, the foam substrate can have moderate softness, and in addition, it becomes a foam that is easy to stretch, and the strength becomes sufficiently high. The more preferred lower limit of the glass transition temperature of the foam substrate is -25°C, and the more preferred upper limit is 20°C.

[0135] The glass transition temperature can be determined using a viscoelasticity measuring device (for example, "Rheometrics Dynamic Analyzer RDA-700" manufactured by Rheometrics) under the conditions of a measuring temperature of -30 to 100°C, a heating rate of 3°C / min, and a frequency of 1 Hz.

[0136] The thickness of the substrate is not particularly limited, but the preferred lower limit is 100 μm, and the preferred upper limit is 2000 μm. If the thickness of the substrate is 100 μm or more, the substrate can have appropriate flexibility. If the thickness of the substrate is 2000 μm or less, sufficient bonding and fixing using an adhesive tape can be achieved. The more preferred lower limit of the thickness of the substrate is 200 μm, and the more preferred upper limit is 1600 μm.

[0137] The thickness of the substrate can be measured using a dial thickness gauge (for example, “ABS Digital Indicator” manufactured by Mitutoyo Corporation).

[0138] The adhesive tape of the present invention may further include a resin sheet integrated with the substrate. By using the resin sheet, the substrate, particularly the foam substrate, can be prevented from being elongated and broken during handling, and reprocessability can be imparted to the adhesive tape.

[0139] The resin constituting the resin sheet is not particularly limited, and examples thereof include polyester resins such as polyethylene terephthalate, polyethylene resins, polypropylene resins, polyvinyl chloride, epoxy resins, silicone resins, phenolic resins, polyimide, polyester, polycarbonate, etc. Among them, polyethylene resins, polypropylene resins, and polyester resins are preferred from the perspective of excellent flexibility. Among polyester resins, polyethylene terephthalate is preferred.

[0140] The thickness of the resin sheet is not particularly limited, but the preferred lower limit is 10 μm, and the preferred upper limit is 100 μm. If the thickness of the resin sheet is 10 μm or more, the resin sheet is not easily broken even when the resin sheet is stretched. If the thickness of the resin sheet is 100 μm or less, the decrease in the followability to the adherend can be suppressed.

[0141] The resin sheet may be colored. By coloring the resin sheet, light-shielding properties can be imparted to the pressure-sensitive adhesive tape.

[0142] The method of coloring the resin sheet is not particularly limited, and examples thereof include a method of mixing particles of carbon black, titanium oxide, or the like or fine bubbles into the resin constituting the resin sheet, and a method of applying ink on the surface of the resin sheet.

[0143] The thickness of the adhesive tape of the present invention is not particularly limited, and the preferred lower limit is 0.3 mm, and the preferred upper limit is 2 mm. If the above thickness is 0.3 mm or more, the adhesive force of the adhesive tape becomes sufficient, and the holding force of the adhesive tape to the load in the shear direction becomes higher. If the above thickness is 2 mm or less, sufficient bonding and fixing using the adhesive tape can be achieved. The more preferred upper limit of the above thickness is 1.7 mm.

[0144] As a method for producing the pressure-sensitive adhesive tape of the present invention, for example, the following method can be mentioned.

[0145] First, a solvent is added to a (meth)acrylic copolymer and, if necessary, a tackifier, a crosslinking agent, etc. to prepare a solution of an adhesive A, which is then applied to the surface of a substrate, and the solvent in the solution is completely dried and removed to form an adhesive layer A. Next, a release film is overlapped on the formed adhesive layer A in a state where its release-treated surface faces the adhesive layer A.

[0146] Next, prepare another release film except the above-mentioned release film, apply the solution of adhesive B on the release treatment surface of the release film, remove the solvent in the solution by complete drying, and thus make a laminated film formed with adhesive layer B on the surface of the release film. The laminated film obtained is overlapped on the back side of the substrate formed with adhesive layer A in a state where adhesive layer B and the back side of the substrate face each other, and make a laminated body. Then, utilize rubber roller etc. to pressurize the above-mentioned laminated body. Thus, it is possible to obtain a double-sided adhesive tape with adhesive layer and the surface of adhesive layer covered by release film on both sides of the substrate.

[0147] Alternatively, two sets of laminated films may be prepared in the same manner, and these laminated films may be overlapped on both sides of a substrate so that the adhesive layer of the laminated film faces the substrate to prepare a laminated body, and the laminated body may be pressurized using a rubber roller, etc. Thus, a double-sided adhesive tape having adhesive layers on both sides of the substrate and the surfaces of the adhesive layers covered with release films may be obtained.

[0148] The adhesive tape of the present invention can be used for any purpose, but can be used, for example, to fix components in electronic devices. The electronic devices are not particularly limited, but examples thereof include televisions, monitors, portable electronic devices, and vehicle-mounted electronic devices.

[0149] Among them, the adhesive tape of the present invention is suitable for fixing components in display devices such as televisions and monitors, especially relatively large display devices, specifically, for example, in the above-mentioned display device, it is used to fix the cover plate on the surface to the housing. The adhesive tape of the present invention can exert a high holding force on the load in the shear direction, and therefore, it is suitable for use even in the case of using a narrow adhesive tape to fix components in a relatively large display device. The adhesive tape of the present invention can be narrow, and its width is not particularly limited, and the preferred lower limit is 1000μm, the preferred upper limit is 10000μm, the more preferred lower limit is 1500μm, and the more preferred upper limit is 5000μm. The shape of the adhesive tape of the present invention in these uses is not particularly limited, and rectangular, frame-shaped, circular, elliptical, annular, etc. can be cited.

[0150] The pressure-sensitive adhesive tape of the present invention can also be used for vehicle interiors, interior and exterior decoration of home appliances (eg, TVs, monitors, air conditioners, refrigerators, etc.), and the like.

[0151] Effects of the Invention

[0152] According to the present invention, it is possible to provide a pressure-sensitive adhesive tape that exhibits a high holding force against a load in a shearing direction. BRIEF DESCRIPTION OF THE DRAWINGS

[0153] Figure 1 It is a schematic diagram showing the cohesive force test of the adhesive layer.

[0154] Figure 2 This is a schematic diagram showing a method for measuring the shear fracture strength of a foam substrate.

[0155] Figure 3 It is a schematic diagram showing the holding force test of the adhesive tape.

[0156] Figure 4 This is a schematic diagram showing a holding force test (glass-SUS shear holding force test) of an adhesive tape (in the case of a foam substrate). DETAILED DESCRIPTION

[0157] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0158] (Example 1)

[0159] (1) Production of Adhesive A (Free Radical Polymerization)

[0160] 155.7 parts by weight of ethyl acetate, 60 parts by weight of butyl acrylate (BA), 16.9 parts by weight of ethyl acrylate (EA), 20 parts by weight of 2-ethylhexyl acrylate (2EHA), 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA), and 3 parts by weight of acrylic acid (AAc) were added to a reactor equipped with a thermometer, a stirrer, and a condenser. After nitrogen substitution, the reactor was set in a water bath set at 60°C, and the reactor was heated to start reflux. 30 minutes after the start of reflux, 0.06 parts by weight of azobisisobutyronitrile as a polymerization initiator was added to the reactor and reacted for 6 hours. Then, ethyl acetate was added to the reactor while diluting and cooling to obtain a solution containing a (meth)acrylic acid copolymer.

[0161] The obtained solution containing the (meth)acrylic acid copolymer was diluted 50 times with tetrahydrofuran (THF), and the obtained dilution was filtered with a filter (material: polytetrafluoroethylene, pore size: 0.2 μm). The obtained filtrate was supplied to a gel permeation chromatograph (manufactured by Waters, 2690 Separations Model), and GPC measurement was performed under the conditions of a sample flow rate of 1 ml / min and a column temperature of 40°C to measure the polystyrene-equivalent molecular weight of the (meth)acrylic acid copolymer, and the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) were obtained. As a column, GPC KF-806L (manufactured by Showa Denko KK) was used, and as a detector, a differential refractometer was used.

[0162] Ethyl acetate was added to 100 parts by weight of the nonvolatile content of the obtained solution containing the (meth)acrylic copolymer and stirred, and the thickener and crosslinking agent shown in Table 1 were added and stirred to obtain an adhesive A having a nonvolatile content of 20% by weight. It should be noted that the amount of the crosslinking agent shown in Table 1 is the solid content relative to the solid content of the adhesive.

[0163] (2) Manufacturing of adhesive tape

[0164] A release film with a thickness of 150 μm was prepared, and adhesive A was applied to the release-treated surface of the release film, and dried at 100°C for 5 minutes to form an adhesive layer with a thickness of 0.05 mm. The adhesive layer was bonded to the surface of a PET film with a thickness of 50 μm. Then, in the same manner, the same adhesive layer as above was bonded to the opposite surface of the PET film after the PET spacer was peeled off. Then, curing was performed by heating at 40°C for 48 hours. Thus, an adhesive tape covered with a release film was obtained.

[0165] (3) Determination of gel fraction

[0166] The adhesive tape was cut into a flat rectangle of 50 mm × 100 mm to prepare a test piece. The test piece was shaken in ethyl acetate at 23°C and 120 rpm for 24 hours. After shaking, the ethyl acetate was separated from the test piece that had absorbed ethyl acetate and swelled using a metal mesh (mesh size #200), and the separated test piece and the metal mesh were dried at 110°C for 1 hour. After drying, the test piece was placed at 23°C for 30 minutes, and after the temperature of the test piece was restored to 23°C, the weight of the test piece was measured, and the gel fraction was calculated using the following formula (1).

[0167] In addition, no release film for protecting the adhesive layer was laminated on the test piece.

[0168] Gel fraction (weight %) = 100 × (W2-W0-W3) / (W1-W0) (1)

[0169] (W0: weight of substrate, W1: weight of test piece before immersion, W2: weight of test piece including metal mesh after immersion and drying, W3: initial weight of metal mesh)

[0170] (4) Cohesion test

[0171] Figure 1 A schematic diagram showing a cohesion test of an adhesive layer is shown. Figure 1As shown, after the adhesive tape 8 is cut into 20mm×40mm, the release film on one side is peeled off, and a 30mm×150mm PET film 12 (FE2002 made by Futamura Chemical Co., Ltd., thickness 23μm) is respectively attached to the two ends of the exposed adhesive layer (the two ends in the length 40mm direction). At this time, the two ends of the adhesive tape 8 are attached to the PET film 12 in a manner that each overlaps 5mm. Then, the center of the adhesive tape 8 is attached to a SUS plate 11 with a width of 5mm heated to 80°C. A 100g weight 13a is fixed to the end of the side of the two PET films 12 that is not attached to the adhesive tape 8. A 200g weight 13b is fixed to the end of one PET film 12, and a static load is applied in the horizontal direction for 3 minutes. The displacement of the adhesive tape 8 in the tensile direction is measured using an electronic micrometer 14, and the displacement is divided by the thickness of the adhesive layer to calculate the displacement of the adhesive layer per 1μm thickness.

[0172] (5) Determination of haze value

[0173] The haze value of the adhesive layer was measured using a haze meter (NDH 4000, manufactured by Nippon Denshoku Industries Co., Ltd.). The measurement sample was prepared by attaching the adhesive layer (thickness 50 μm) applied to a spacer to a glass plate (S1214 MICRO SLIDE GLASS, manufactured by Matsunami Glass Industries Co., Ltd.) and then peeling off the spacer.

[0174] (6) Determination of volatile components

[0175] The weighed pressure-sensitive adhesive tape was heated at 90° C. for 30 minutes using a thermal desorption device (Gerstel TDS manufactured by Gestel). The amount of volatile components released during this time was measured using a GC-MS device (Agilent 6890GC / 5973MSD manufactured by Agilent Technologies), and the content of the volatile components was calculated using the following formula (2).

[0176] Content of volatile components (ppm) = Total amount of volatile components derived from monomers of the (meth)acrylic copolymer constituting the adhesive layer (μg) / weight of adhesive before heating (g) (2)

[0177] It should be noted that the weight of the adhesive before heating is obtained by finding the ratio of the weight of the PET film as the base material in the adhesive tape and subtracting the weight of the base material from the weight of the adhesive tape (weight of adhesive = weight of adhesive tape - weight of base material). For the PET film, it was confirmed in advance that the volatile components derived from the monomers constituting the (meth)acrylic acid copolymer contained in the adhesive layer were not released.

[0178] (Examples 2 to 18)

[0179] A pressure-sensitive adhesive tape was obtained in the same manner as in Example 1 except that the monomer mixture, the tackifier, and the crosslinking agent were changed as shown in Tables 1 to 2.

[0180] (Examples 19 to 21)

[0181] A pressure-sensitive adhesive tape was obtained in the same manner as in Example 1 except that the pressure-sensitive adhesive was changed as described below. In Examples 19, 20, and 21, pressure-sensitive adhesives B1, B2, and B3 were used, respectively.

[0182] (Manufacture of Adhesives B1, B2 and B3 (Free Radical Polymerization))

[0183] In a reactor equipped with a thermometer, a stirrer, and a condenser, in the case of adhesive B1, 155.7 parts by weight of ethyl acetate, 47.5 parts by weight of butyl acrylate (BA), 47.5 parts by weight of 2-ethylhexyl acrylate (2EHA), 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA), and 5 parts by weight of acrylic acid (AAc) were added. After nitrogen substitution, the reactor was set in a water bath set at 60°C, and the reactor was heated to start reflux. 30 minutes after the start of reflux, 0.06 parts by weight of azobisisobutyronitrile as a polymerization initiator was added to the reactor and reacted for 3.5 hours. Then, ethyl acetate was added to the reactor while diluting and cooling, thereby obtaining a solution containing a (meth)acrylic acid copolymer.

[0184] In the same manner as above, the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the (meth)acrylic copolymer were determined.

[0185] Ethyl acetate was added to 100 parts by weight of the nonvolatile content of the obtained solution containing the (meth)acrylic copolymer and stirred, and the tackifier and crosslinking agent shown in Table 2 were added and stirred to obtain an adhesive B having a nonvolatile content of 20% by weight.

[0186] In addition, in the case of the adhesives B2 and B3, the monomer mixture was changed as shown in Table 2.

[0187] (Comparative Examples 1 and 2)

[0188] Except having changed the monomer mixture, tackifier, and crosslinking agent as shown in Table 3, it carried out similarly to Example 1, and obtained the adhesive tape.

[0189] (Comparative Example 3)

[0190] A pressure-sensitive adhesive tape was obtained in the same manner as in Example 1 except that the pressure-sensitive adhesive was changed as described below.

[0191] (Manufacturing of Adhesive C (Free Radical Polymerization))

[0192] Ethyl acetate as a polymerization solvent was added to the reactor, and after bubbling with nitrogen, the reactor was heated while nitrogen was flowing in, and reflux was started. Next, a polymerization initiator solution obtained by diluting 0.1 parts by weight of a polymerization initiator (azobisisobutyronitrile) by 10 times with ethyl acetate was added to the reactor. Next, 60 parts by weight of butyl acrylate (BA), 16.9 parts by weight of ethyl acrylate (EA), 20 parts by weight of 2-ethylhexyl acrylate (2EHA), 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA), and 3 parts by weight of acrylic acid (AAc) were added dropwise over 2 hours. After the dropwise addition was completed, a polymerization initiator solution obtained by diluting 0.1 parts by weight of a polymerization initiator (azobisisobutyronitrile) by 10 times with ethyl acetate was added to the reactor again, and a polymerization reaction was carried out for 4 hours to obtain a solution containing a (meth)acrylic acid copolymer.

[0193] In the same manner as above, the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the (meth)acrylic copolymer were determined.

[0194] Ethyl acetate was added to 100 parts by weight of the nonvolatile content of the obtained solution containing the (meth)acrylic copolymer and stirred, and the thickener and crosslinking agent shown in Table 3 were added and stirred to obtain an adhesive C having a nonvolatile content of 30% by weight.

[0195] (Comparative Example 4)

[0196] A pressure-sensitive adhesive tape was obtained in the same manner as in Example 1 except that the pressure-sensitive adhesive was changed as described below.

[0197] (Manufacturing of Adhesive D (Free Radical Polymerization))

[0198] Ethyl acetate as a polymerization solvent and half of the monomer mixture were added to the reactor, and after bubbling with nitrogen, the reactor was heated to start reflux. After ethyl acetate boiled, 0.05 parts by weight of azobisisobutyronitrile as a polymerization initiator was added 30 minutes later. The remaining half of the monomer mixture was evenly and slowly added dropwise over 1 hour to react. As the monomer mixture, 60 parts by weight of butyl acrylate (BA), 16.9 parts by weight of ethyl acrylate (EA), 20 parts by weight of 2-ethylhexyl acrylate (2EHA), 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA) and 3 parts by weight of acrylic acid (AAc) were used. 0.07 parts by weight of azobisisobutyronitrile was added 30 minutes after the addition was completed, and the polymerization reaction was further carried out for 4 hours. Ethyl acetate was added to the reactor while diluting and cooling was performed, thereby obtaining a solution containing a (meth)acrylic acid copolymer.

[0199] In the same manner as above, the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the (meth)acrylic copolymer were determined.

[0200] Ethyl acetate was added to 100 parts by weight of the nonvolatile content of the obtained solution containing the (meth)acrylic copolymer and stirred, and the thickener and crosslinking agent shown in Table 3 were added and stirred to obtain an adhesive D having a nonvolatile content of 30% by weight.

[0201] (Comparative Example 5)

[0202] A pressure-sensitive adhesive tape was obtained in the same manner as in Example 1 except that the pressure-sensitive adhesive was changed as described below.

[0203] (Manufacturing of Adhesive E (Free Radical Polymerization))

[0204] Ethyl acetate as a polymerization solvent and half of the monomer mixture were added to the reactor, and after bubbling with nitrogen, the reactor was heated to start reflux. After ethyl acetate boiled, 0.05 parts by weight of azobisisobutyronitrile as a polymerization initiator was added 30 minutes later. The remaining half of the monomer mixture was evenly and slowly added dropwise over 1 hour to react. As the monomer mixture, 100 parts by weight of 2-ethylhexyl acrylate (2EHA), 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA) and 3 parts by weight of acrylic acid (AAc) were used. 0.07 parts by weight of azobisisobutyronitrile was added 30 minutes after the addition was completed, and the polymerization reaction was further carried out for 4 hours. Ethyl acetate was added to the reactor while diluting and cooling, thereby obtaining a solution containing a (meth)acrylic acid copolymer.

[0205] In the same manner as above, the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the (meth)acrylic copolymer were determined.

[0206] Ethyl acetate was added to 100 parts by weight of the nonvolatile content of the obtained solution containing the (meth)acrylic copolymer and stirred, and the thickener and crosslinking agent shown in Table 3 were added and stirred to obtain an adhesive E having a nonvolatile content of 30% by weight.

[0207] (Comparative Example 6)

[0208] A pressure-sensitive adhesive tape was obtained in the same manner as in Example 1 except that the pressure-sensitive adhesive was changed as described below.

[0209] (Manufacturing of Adhesive F (Living Radical Polymerization))

[0210] Tellurium (40 mesh, tellurium metal, manufactured by Aldrich) 6.38 g (50 mmol) was suspended in tetrahydrofuran (THF) 50 mL, and 1.6 mol / L n-butyl lithium / hexane solution (manufactured by Aldrich) 34.4 mL (55 mmol) was slowly added dropwise at room temperature. The reaction solution was stirred until the tellurium metal disappeared completely. Ethyl-2-bromo-isobutyrate 10.7 g (55 mmol) was added to the reaction solution at room temperature and stirred for 2 hours. After the reaction was completed, the solvent was concentrated under reduced pressure, and then vacuum distillation was performed to obtain 2-methyl-2-n-butyltelluryl-propionic acid ethyl ester (Japanese: 2-methyl-2-n-butyltelluryl-propionic acid ethyl ester) as a yellow oil.

[0211] In a glove box replaced with argon, 38 μL of the obtained ethyl 2-methyl-2-n-butyltelluryl-propionate, 2.8 mg of V-60 (2,2'-azobisisobutyronitrile, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 1 mL of ethyl acetate were added to the reaction container, and then the reaction container was sealed and taken out of the glove box. Next, while argon gas was flowed into the reaction container, 66.5 g of ethyl acetate as a polymerization solvent was added to the reaction container relative to 100 g of the monomer mixture, and a polymerization reaction was carried out at 60°C for 20 hours to obtain a solution containing a (meth)acrylic acid copolymer. As the monomer mixture, 100 parts by weight of 2-ethylhexyl acrylate (2EHA), 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA), and 3 parts by weight of acrylic acid (AAc) were used.

[0212] In the same manner as above, the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the (meth)acrylic copolymer were determined.

[0213] Ethyl acetate was added to 100 parts by weight of the nonvolatile content of the obtained solution containing the (meth)acrylic copolymer and stirred, and the thickener and crosslinking agent shown in Table 3 were added and stirred to obtain an adhesive F having a nonvolatile content of 30% by weight.

[0214] <Evaluation>

[0215] The pressure-sensitive adhesive tapes obtained in Examples and Comparative Examples were evaluated as follows. The results are shown in Tables 1 to 3.

[0216] (1) Holding force test

[0217] Figure 3 A schematic diagram showing a holding force test of an adhesive tape is shown. Figure 3 (a) is the front view, Figure 3 (b) is a side view. Figure 3As shown in (a) and (b), an adhesive tape 3 backed by a PET film (#50) 4 is attached to a SUS plate 1 and a SUS plate 2 to prepare a holding force test sample in which the attachment area between the SUS plate 1 and the adhesive tape 3 is 25 mm×25 mm. The holding force test sample is prepared as follows.

[0218] First, prepare SUS plate 1 (thickness 2mm×50mm×70mm, made by uniformly grinding the surface of SUS304 steel plate specified in JIS-G-4305 with water-resistant grinding paper No. 360) and SUS plate 2 (thickness 1mm×30mm×50mm, unground). Wash SUS plate 1 and SUS plate 2 with ethanol and dry them thoroughly. Cut the adhesive tape 3 into a width of 25mm×length of 140mm, peel off the release film on one side, and stick a PET film (#50) 4 on the exposed adhesive layer. Next, peel off the release film on the other side, stick the end of the exposed adhesive layer to SUS plate 1 in a way that does not allow bubbles to enter, and press-bond with a 2kg rubber roller reciprocating once at a speed of 10mm / second. At this time, stick the SUS plate 1 and the adhesive tape 3 in a way that the overlap is 30mm. In addition, the end of the adhesive layer on the opposite side to the end attached to the SUS plate 1 was attached to the SUS plate 2, and a 2 kg rubber roller was reciprocated once at a speed of 10 mm / second to perform pressure bonding. At this time, the adhesive tape 3 was arranged so as to cover the front and back sides of the SUS plate 2. Then, a through hole 5 was provided on the adhesive tape 3 together with the SUS plate 2, and the adhesive tape 3 was cut so that the attached area of ​​the SUS plate 1 and the adhesive tape 3 became 25 mm×25 mm.

[0219] After the holding force test sample prepared as described above was placed in a thermostatic chamber at 50°C and 80% RH for 24 hours, a 3 kg weight 6 was installed in the through hole 5 under the same environment, and the time (peeling time) until the weight 6 fell was measured. The case where the weight 6 did not fall for more than 200 hours was indicated as ○, and the case where it fell for less than 200 hours was indicated as ×.

[0220] For Examples 1 to 21 in which the peeling time was 200 hours or more, the holding strength test sample prepared in the same manner as above was placed in a constant temperature chamber at 50° C. and 80% RH for 24 hours, and then a 3 kg weight 6 was installed in the through hole 5 under the same environment, and the movement (mm) of the adhesive tape 1 after 500 hours was measured.

[0221] (2) 180° peel test

[0222] According to JIS Z 0237, a 180° peel test was performed. First, the adhesive tape was cut into a width of 25 mm × a length of 250 mm, the release film on one side was peeled off, and a PET film (#50) was attached to the exposed adhesive layer. Next, the release film on the other side was peeled off, and the end of the exposed adhesive layer was attached to a SUS plate (thickness 2 mm × 50 mm × 70 mm, the surface of the SUS304 steel plate specified in JIS-G-4305 was evenly polished with water-resistant abrasive paper No. 360) in a way that bubbles did not enter, and a 2 kg rubber roller was reciprocated once at a speed of 10 mm / second for crimping. After leaving it for 20 minutes, the adhesive tape was peeled off in the 180° direction (folding direction) at a speed of 300 mm / minute using a tensile testing machine, and the peeling force was measured. The peeling force of 20N or more is indicated as ◎, the peeling force of 17N or more and less than 20N is indicated as 0, and the peeling force of less than 17N is indicated as △.

[0223] (3) Productivity (polymerization time of (meth)acrylic acid copolymer)

[0224] The productivity was evaluated by the polymerization time of the (meth)acrylic acid-based copolymer. A polymerization time of 5 hours or less was indicated as ◎, a polymerization time of 5 hours or more and less than 15 hours was indicated as ○, and a polymerization time of 15 hours or more was indicated as ×.

[0225] (4) Holding force test in case of foam substrate (glass-SUS shear holding force test)

[0226] A foam substrate adhesive tape was obtained in the same manner as in the Examples and Comparative Examples except that the PET film with a thickness of 50 μm as the substrate was replaced with a foam substrate having a shear fracture strength shown in Tables 1 to 3. Figure 2 Determined by the method shown.

[0227] Figure 4A schematic diagram showing the holding force test (glass-SUS shear holding force test) of the adhesive tape (in the case of a foam substrate) is shown. The foam substrate adhesive tape is cut into 25 mm × 25 mm to make a test piece 22, and one release film is peeled off to expose the adhesive layer. After the test piece 22 is placed on the glass plate 21 in a state where the adhesive layer and the glass plate 21 are facing each other, a 2 kg rubber roller is reciprocated once on the test piece 22 at a speed of 300 mm / min under the condition of 23°C, thereby bonding the test piece 22 to the glass plate 21. Then, the other release film of the test piece 22 is peeled off to expose the adhesive layer. After the SUS plate 23 is placed on the test piece 22 in a state where the SUS plate 23 is facing the adhesive layer, it is pressed with a 5 kg weight for 10 seconds to make it pressed, and it is left to stand for 24 hours under the conditions of 23°C and 50% RH, thereby making a test sample.

[0228] like Figure 4 As shown, a weight 24 of 500 g, 1.5 kg, 3 kg or 4 kg is installed to apply a load to the test sample in the horizontal direction, and the time until the weight falls is measured under the conditions of 60°C and 90% RH. The case where the weight does not fall for more than 500 hours is indicated as ○, and the case where it falls for less than 500 hours is indicated as ×.

[0229] [Table 1]

[0230]

[0231] [Table 2]

[0232]

[0233] [Table 3]

[0234]

[0235] In addition, the details of the thickeners and cross-linking agents shown in Tables 1 to 3 are as follows.

[0236] · Tackifier D135 (hydroxyl value 45, polymerized rosin ester, made by Arakawa Chemical Industries, Ltd.)

[0237] · Tackifier KE359 (hydroxyl value 42, hydrogenated rosin, made by Arakawa Chemical Industries, Ltd.)

[0238] · Tackifier A115 (hydroxyl value 15, non-uniformized rosin, made by Arakawa Chemical Industries, Ltd.)

[0239] · Thickener G150 (hydroxyl value 135, terpene phenol, manufactured by Yasuhara Chemical Co., Ltd.)

[0240] · Cross-linking agent Coronate L-45 (isocyanate cross-linking agent, manufactured by Tosoh Corporation)

[0241] Industrial Applicability

[0242] According to the present invention, it is possible to provide a pressure-sensitive adhesive tape that exhibits a high holding force against a load in a shearing direction.

[0243] Description of Reference Numerals

[0244] 1 SUS board

[0245] 2 SUS board

[0246] 3 Adhesive tape

[0247] 4 PET film (#50)

[0248] 5 Through holes

[0249] 6 Heavy objects (3kg)

[0250] 8 Adhesive tape

[0251] 11 SUS board

[0252] 12 PET film

[0253] 13a Heavy object (100g)

[0254] 13b Heavy object (200g)

[0255] 14 Electronic micrometer

[0256] 18 Test piece (adhesive tape)

[0257] 19 SUS plate

[0258] 21 Glass Pane

[0259] 22 Test piece (foam-based adhesive tape)

[0260] 23 SUS plate

[0261] 24 weights (500g, 1.5kg, 3kg or 4kg)

Claims

1. An adhesive tape, characterized in that: having an adhesive layer, The adhesive layer has a gel fraction of 25 wt % or more and 70 wt % or less, and a displacement per 1 μm thickness of the adhesive layer measured at 80° C. using a cohesion tester is 3.8 μm or less, The adhesive layer contains a (meth)acrylic acid copolymer, The (meth)acrylic acid-based copolymer contains a structural unit derived from n-butyl acrylate, The (meth)acrylic acid-based copolymer does not contain a structural unit derived from 2-ethylhexyl acrylate, or the content of the structural unit derived from 2-ethylhexyl acrylate in the (meth)acrylic acid-based copolymer is 60% by weight or less, The (meth)acrylic acid-based copolymer has a weight average molecular weight Mw of 1,000,000 or more and 2,000,000 or less, The (meth)acrylic acid-based copolymer has a ratio of a weight average molecular weight Mw to a number average molecular weight Mn, that is, a molecular weight distribution Mw / Mn of 4.5 or less.

2. The adhesive tape according to claim 1, characterized in that The pressure-sensitive adhesive layer contains a (meth)acrylic copolymer and a tackifier, wherein the (meth)acrylic copolymer contains a structural unit derived from an alkyl (meth)acrylate having an alkyl group having 3 or less carbon atoms in an amount of 20% by weight or less.

3. The adhesive tape according to claim 2, characterized in that The (meth)acrylic acid-based copolymer contains a structural unit derived from acrylic acid in an amount of 3% by weight or more.

4. The adhesive tape according to claim 2 or 3, characterized in that: The content of the tackifier having a hydroxyl value of 35 or more is 60% by weight or more relative to the total weight of the tackifier.

5. The adhesive tape according to claim 1, 2 or 3, characterized in that: The haze value of the adhesive layer is 30% or less.

6. The adhesive tape according to claim 1, 2 or 3, characterized in that: It also has a foam substrate.

7. The adhesive tape according to claim 6, characterized in that The shear fracture strength of the foam substrate is 80 N / 25 mm or more.

8. The adhesive tape according to claim 1, 2 or 3, characterized in that: It is used to fix components in electronic equipment.

Citation Information

Patent Citations

  • Impact-absorbing tape

    JP2009242541A

  • Pressure-sensitive adhesive sheet for front plate of display device

    JP2009258274A

  • Adhesive sheet for electronic devices

    CN105518094A

  • Double-sided pressure-sensitive adhesive tape

    CN107709494A

  • Adhesive tape

    JP2015145510A